Impact of COVID‐19 on inpatient referral of acute heart failure: a single‐centre experience from the south‐west of the UK. (6th January 2021) - Doolub, Gemina; Wong, Chih; Hewitson, Lynsey; Mohamed, Ahmed; Todd, Fraser; Gogola, Laisha; Skyrme‐Jones, Andrew; Aziz, Shahid; Sammut, Eva; Dastidar, Amardeep
Abstract: Aims: Healthcare services worldwide have been significantly impacted by the COVID‐19 pandemic. Recent reports have shown a decline in hospitalization for emergency cardiac conditions. The impact of the COVID‐19 pandemic on hospitalization and particularly mortality due to acute heart failure has not been thoroughly described. Methods and results: In this single‐centre observational study, we examined referrals to the acute heart failure team over a period of 16 weeks (7 January to 27 April 2020) spanning the ongoing COVID‐19 pandemic; 283 patients referred to our acute heart failure services over the study period were included on the basis of typical symptoms, raised BNP, and echocardiogram. There was a substantial but statistically non‐significant drop in referrals with 164 referred in the 8 weeks before the first UK death due to COVID‐19 on 2 March 2020 (BC), compared with 119 referred after (AC) in the subsequent 8 weeks, representing a 27% reduction overall ( P = 0.06). The 30 day case fatality rate was increased from 11% in the BC group compared with 21% in the AC group (risk ratio = 1.9, 95% confidence interval 1.09–3.3). Age, gender, length of stay, left ventricular ejection fraction, and N‐terminal pro‐brain natriuretic peptide were similar between the groups. Admission creatinine, age, and AC cohort status were found to be univariable predictors of mortality. On multivariate Cox regression analysis, only age (hazard ratio 1.04, P = 0.03) and AC cohort status (hazard ratio 2.1, P = 0.017) remained significant predictors of mortality. On sensitivity analysis, this increased mortality was driven by COVID‐19 positive status. Conclusions: There was a reduction in referral of patients with acute heart failure with significant increase in mortality in the 8 weeks following the first reported UK death due to COVID‐19. The observation of increased mortality does not appear related to a change in population in terms of demographics, left ventricular ejection fraction, or N‐terminal pro‐brain natriuretic peptide. The observed increased mortality appears to be related to the coexistence of COVID19 infection with acute heart failure. The study highlights the need for widespread preventative and shielding measures particularly in this group of patients especially in the light of the second wave. Longer follow‐up with inclusion of data from other centres and community heart failure services will be needed.